Chronography of the Milky Way's Halo System with Field Blue Horizontal-branch Stars - Santucci, Rafael M. (2015)
In a pioneering effort, Preston et al. reported that the colors of bluehorizontal-branch (BHB) stars in the halo of the Galaxy shift withdistance, from regions near the Galactic center to about 12 kpc away,and interpreted this as a correlated variation in the ages of halostars, from older to younger, spanning a range of a few Gyrs. We haveapplied this approach to a sample of some 4700 spectroscopicallyconfirmed BHB stars selected from the Sloan Digital Sky Survey toproduce the first ?chronographic map? of the halo of theGalaxy. We demonstrate that the mean de-reddened g ‑ r color, <{(g-r)}0> , increases outward in the Galaxy from‑0.22 to ‑0.08 (over a color window spanning [‑0.3:0.0]) from regions close to the Galactic center to ∼40 kpc,independent of the metallicity of the stars. Models of the expectedshift in the color of the field BHB stars based on modern stellarevolutionary codes confirm that this color gradient can be associatedwith an age difference of roughly 2?2.5 Gyr, with the oldest starsconcentrated in the central ∼15 kpc of the Galaxy. Within thiscentral region, the age difference spans a mean color range of about0.05 mag (∼0.8 Gyr). Furthermore, we show that chronographic mapscan be used to identify individual substructures, such as theSagittarius Stream, and overdensities in the direction of Virgo andMonoceros, based on the observed contrast in their mean BHB colors withrespect to the foreground/background field population.